Piezoelectric domain walls in van der Waals antiferroelectric CuInP2Se6 - Andrius Dziaugys (Nature Portfolio, 2020)
Domain walls in van der Waals layered ferrielectric CuInP2Se6 exhibit piezoelectric response. This striking departure from traditional ferroelectric behavior is ascribed to a partially polarized antiferroelectric state, where the domain wall separates coexisting regions of ferrielectric and antiferroelectric phases.